Advantages and training techniques of left-handed manipulation in laparoscopic radical resection of right-sided colon cancer and rectal cancer - Lin Yueying; Yang Ting; An Liya; Qi Yuxing; Shi Yanmei; Sun Dali (结直肠肛门外科)
Laparoscopic surgery is currently the primary surgical approach for the treatment of colorectal cancer. Due to factors such as anatomical characteristics of adjacent tumor sites, tumor size, and Trocar distribution, it is not easy for most right-handed surgeons to smoothly perform high-quality laparoscopic radical resection of colorectal cancer. Therefore, it is crucial to train the coordination of two-handed manipulation during laparoscopic surgery, particularly left-handed manipulation. Enhancing the flexibility of left-handed manipulation can streamline the surgical process. Based on the clinical practice experience of our team, this article takes laparoscopic radical resection of right-sided colon cancer and laparoscopic radical resection of rectal cancer as examples. It points out the difficulties and causes encountered during right-handed manipulation during surgery, discusses the advantages of left-handed manipulation, and proposes methods and suggestions for optimizing left-handed manipulation training.